DIGITAL TRANSFORMATION PROCESSES OF BANKING SERVICES IMPROVEMENT - Akbarov Jasurbek Akrambekovich; Gulomova Nigora Farkhod kizi (TADQIQOTLAR.UZ, 2024)
Abstract. Digital transformation of retail banking services, service channels in digital banks, analysis of statistical data on the types and volume of retail loans, and the experience of developed countries in the development of retail banking services are covered. During the preparation of the scientific work, the methods of data comparison, data grouping, and expert evaluation were effectively used, and the authors' conclusions and suggestions on the development of retail banking services in the process of digital transformation were presented.